FULFILLING THE WORKERS 'RIGHTS IN THE PANDEMIC TIME OF COVID-19 - Iskatrinah, Iskatrinah; Dewi Setia Triana, Ikama; Erowati, Eti Mul (Jurnal Pendidikan Kewarganegaraan Undiksha, 2020)
In terms of wage protection and protection for workers in the workplace, the entrepreneur can postpone the payment of wages (if the entrepreneur is unable to pay the wage according to the minimum wage), by first conducting negotiations with the worker / laborer or trade / labor union regarding the suspension. The postponement of the payment of the minimum wage by the employer to the worker / laborer does not automatically eliminate the obligation of the entrepreneur to pay the difference in the minimum wage during the suspension period. To deal with and overcome the crisis caused by the corona virus outbreak or COVID-19, on March 31, 2020, President Joko Widodo has issued Government Regulation in Lieu of Law (PERPU) No. 1 of 2020 concerning “State Financial Policy and Financial System Stability for Handling the Corona Virus Desease 2019 (Covid-19) Pandemic and / or in the context of Facing Threats that Endanger the National Economy and / or Financial System Stability. However, PEPRU No.1 / 2020 has not fully accommodated those related to the world of labor. Affairs related to labor are entirely in the hands of the company and it is risky to cause company arbitrariness